Effect of manual therapy on pain and electromyographic activity of masticatory muscles in patients with temporomandibular disorders - Britto, Priscila Bageston de; Bisi, Maurício André; Dhein, William (Manual Therapy, Posturology & Rehabilitation Journal, 2019)
Background: Temporomandibular disorders (TMD) are disorders of multifactorial origin that affect the temporomandibular joint and/or masticatory muscles. The TMD can generate compensations where physical therapy acts through myofascial releases and joint mobilizations to restore functionality. Objective: To verify the effects of manual therapy techniques on pain and electromyographic activity (EMG) of masticatory muscles in TMD patients. Methods: This is a quasi-experimental study composed of 10 subjects with TMD and 10 healthy subjects who underwent a session of myofascial release, joint mobilization and digit-pressure on the masticatory and cervical muscles. Pain levels and electromyographic activities of the temporal and masseter muscles were bilaterally assessed during the following situations: (1) Maximum Occlusion and (2) Chewing in the right and the left side with chewing gum. Data analysis was performed using BIOMEC-SAS software, in which the data were filtered with a 4th order Butterworth bandpass filter with 20-400hz and normalized as a percentage of maximum occlusion. Data were divided into homolateral and contralateral muscles alongside chewing. EMG variables were compared by factorial ANOVA, and pain by dependent t-test. Results: TMD patients had pain level reduction during maximum occlusion (Pre:4.55±2.2; Post:2.55±1.6; p=<0.001), right chewing (Pre:2.3±2.16; Post:0.4±0.69; p = 0.02) and left chewing (Pre: 1.0±1.15; Post:0.10±0.31; p = 0.05). There was no effect of manual therapy techniques on the EMG activity bilaterally of the temporal (p = 0.617) and masseter (p = 0.926) muscles during chewing. Patients with TMD had higher EMG activities during chewing on the homolateral temporal (p = 0.001) and masseter (0.004) muscles compared to subjects without injury. Conclusion: Manual therapy techniques reduced pain level in TMD patients. No changes in EMG activity were observed after manual therapy techniques. Finally, the study provides evidence of the influence of manual therapy techniques on short-term pain.